Expression of the Ets-1 proto-oncogene in human gastric carcinoma: correlation with tumor invasion. - Nakayama, T. (1996)
The proto-oncogene Ets-1 is a transcription factor known to control the expression of a number of genes involved in extracellular matrix remodeling and has been postulated to play a role in cell migration and tumor invasion. To elucidate the involvement of Ets-1 in human gastric carcinomas, we examined 11 cases of gastric adenoma and 110 cases of gastric carcinoma by immunohistochemistry and compared the degree of Ets-1 expression with the depth of carcinoma invasion. Ets-1 was not expressed either in the normal gastric epithelium or in gastric adenomas. Among the 110 cases with gastric adenocarcinoma, 70 (63.6%) showed positive staining for the Ets-1 protein. In mucosal carcinomas, only 3 of 26 cases (11.5%) showed positive immunostaining for Ets-1. In contrast, 67 of 84 cases (79.8%) with submucosal or more invasive carcinomas showed immunopositivity and intense staining for Ets-1 in the tumor cells. The pattern of Ets-1 immunostaining in mucosal carcinomas was weak and differed from that of other local invasive carcinomas (P < 0.001). Histologically, signet-ring cell and mucinous carcinomas expressed relatively weak positivity for Ets-1. Ets-1 expression correlated significantly with the presence of lymph node metastasis (P < 0.001). In situ hybridization, using an Ets-1 oligonucleotide probe, also confirmed the presence of Ets-1 mRNA in gastric carcinomas. Expression of Ets-1 mRNA was also detected in four different kinds of cultured human gastric carcinoma cell lines by the reverse transcription polymerase chain reaction method. These findings suggest that Ets-1 is overexpressed in gastric mucosal cells that have undergone malignant conversion and that Ets-1 is one of the factors involved in the penetration of gastric carcinoma beyond the muscularis mucosa.